Transcription from the BamHI J fragment of herpes simplex virus type 1 (KOS). - Betz, J L (1983)
RNA transfer experiments (Northern analyses) were used to localize polyadenylated mRNA species made after herpes simplex virus type 1 infection to EcoRI and BamHI fragments and subfragments from the short unique region of the herpes simplex virus type 1 (KOS) genome. Three predominant early mRNAs of 2.5, 1.3, and 0.9 kilobases map in the BamHI J fragment. A detailed restriction map of the BamHI J fragment was constructed.